2021
DOI: 10.1183/23120541.00114-2021
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of angiotensin-(1–7) in severely ill COVID-19 patients

Abstract: The monocarboxypeptidase angiotensin-converting enzyme 2 (ACE2) is a major player in the the renin–angiotensin system (RAS) as it converts the decapeptide angiotensin (Ang) I to Ang-(1–9) and Ang II to Ang-(1–7) (figure 1a) [1]. ACE2 is also a target for the new human coronavirus SARS-CoV-2, which is responsible for the dramatic ongoing COVID-19 pandemic [2]. It has been suggested that following SARS-CoV-2/ACE2 internalisation, Ang II level increases [3] in parallel to a decrease of Ang-(1–7) level [4]. These … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…An investigation found significantly lower activity in COVID-19 patients with respect to controls [79], while other studies found opposite trends [90] or no differences [93]. Opposite results were also observed for the levels of circulating Ang- (1)(2)(3)(4)(5) in two studies: a reduction of about 80% in the COVID-19 class with respect to controls [86], or a 100% increase [82] (see Supplementary Table S1). S1).…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 89%
See 3 more Smart Citations
“…An investigation found significantly lower activity in COVID-19 patients with respect to controls [79], while other studies found opposite trends [90] or no differences [93]. Opposite results were also observed for the levels of circulating Ang- (1)(2)(3)(4)(5) in two studies: a reduction of about 80% in the COVID-19 class with respect to controls [86], or a 100% increase [82] (see Supplementary Table S1). S1).…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 89%
“…The meta-analysis that we carried out in the previous section has shed some light on these questions to a certain extent, but many points remain obscure. Indeed, the experimental and clinical data that we collected from the literature about e.g., the levels of proteins and peptides involved in RAS and the activity of the enzymes, partially disagree [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ang-(1-7) might protect against COVID-19. Specifically, increases in the circulating levels of ACE2 [ 36 ] and Ang-(1-7) [ 37 ] among COVID-19 patients could be a protective mechanism. This notion is supported by Wang et al, who showed that a high Ang-(1-7)/Ang II ratio predicts favorable outcomes in patients with heart failure [ 38 ].…”
Section: Angiotensin 1-7mentioning
confidence: 99%